2006
DOI: 10.1111/j.1369-7625.2006.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Has patients’ involvement in the decision‐making process changed over time?

Abstract: Objective To get insight into the changes over time of patients' involvement in the decision-making process, and into the factors contributing to patients' involvement and general practitioners' (GPs) communication related to the Medical Treatment Act (MTA) issues: information about treatment, other available treatments and side-effects; informed decision making; asking consent for treatment.Background Societal developments have changed the doctorpatient relationship recently. Informed decision making has beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 31 publications
2
71
1
1
Order By: Relevance
“…Some studies show that the variability in patient choice could be anticipated from demographic factors such as age and educational level, meaning the higher the education, the higher of the desire for participation, and the older the patient, the lower the desire for participation [ [12][13][14][15][16], but this finding is not consistent [ 7 17 ].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Some studies show that the variability in patient choice could be anticipated from demographic factors such as age and educational level, meaning the higher the education, the higher of the desire for participation, and the older the patient, the lower the desire for participation [ [12][13][14][15][16], but this finding is not consistent [ 7 17 ].…”
Section: Introductionmentioning
confidence: 81%
“…Search in the literature has revealed only sparse facts about the effect of age on preferences for patient participation, and the most fragile group presented in this study has not been covered in the literature to date. A study in the context of primary care [14] concluded that more informed decision making was observed in 2001 than in 1987, but that observation did not apply to the elderly. Other factors as mentioned above, including health literacy and Internet use, will change, but patients who are ill and old with mental and physical fatigue will always be in a subordinate position and find it difficult to actively participate in medical decisions.…”
Section: Cohort Effectmentioning
confidence: 99%
“…25 These inequalities exist with respect to a variety of health problems, 26 with links to reduced survival rates suggested for older patients with ovarian cancer. 27 The literature regarding shared decision making for older patients is generally sparse, 6,28 but it reports variability in their desire 29,30 and frequency 31 of participation, when compared with younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…They should ascertain just what information their patients want. 8 And GPs and practice nurses may need more specific training to deliver shared decision making. 9 What the present lack of 'shared' in the decision making means for compliance, for example, requires further study.…”
Section: How To Proceed In Practicementioning
confidence: 99%